ANALYSIS OF FINANCIAL WORTHINESS IN TILAPIA FARMING AMONG FARMERS’ GROUP IN NAKHON PATHOM PROVINCE - Puapornpong, Tanatip; Kumpiranont, Piyada; Chaichana, Rapeeporn (RMUTT Global Business and Economics Review, 2023)
This research aims to achieve the following objectives: 1) Study the investment and expenditure associated with raising the tilapia chain among farmers in Nakhon Pathom Province. 2) Examine the costs and returns involved in farming along the tilapia chain among farmers in Nakhon Pathom Province. 3) Analyze the financial viability of tilapia farming throughout the chain among farmers in Nakhon Pathom Province. To conduct this study, a mixed-method research methodology was employed. Quantitative research was conducted using samples of farmers registered with the Provincial Fisheries Office, divided into two groups. Group 1 comprised 16 farmers who were not certified with the Nil Tilapia Farm Standard in Nakhon Pathom Province. Group 2 consisted of 16 farmers who were certified with the GAP standard and had received safety level certification for their tilapia farms in Nakhon Pathom Province. For qualitative research, in-depth interviews were conducted with six relevant scholars, including fishery academicians, commerce academicians from Nakhon Pathom Province, and financial or accounting academicians. The study results revealed the following findings: 1) The average investment in tilapia chain farming among farmers in Nakhon Pathom Province was 390,781.25 baht, with an average raising cost of 216,187.50 baht. A statistical analysis comparing the investment cost and raising cost between the two groups of farmers did not yield any significant differences. 2) The average raising cost of tilapia chains among farmers in Nakhon Pathom Province was 412,781.25 baht, with an average net return of 1,595,875 baht and an average return on investment (ROI) of 102.01%. No statistically significant differences were found when comparing the costs and net returns between the two groups of farmers. However, a statistically significant difference was observed at the .01 level when considering the return on investment between the two groups. Specifically, the group of certified farmers had a higher return. 3) The integrated method emerged as an effective approach to reducing costs and increasing efficiency in tilapia production, thereby creating financial viability in the tilapia chain among farmers in Nakhon Pathom Province. Key strategies for achieving this include focusing on product processing, collaborating with fish-buying farms, reducing the cost of fish feed, implementing fish size control techniques, ensuring water quality, and exploring both fresh and processed markets where farmers can engage in direct trading.